1H, 13C and 15N resonance assignments for the microtubule-binding domain of the kinetoplastid kinetochore protein KKT4 from Trypanosoma brucei - Redfield, C; Akiyoshi, B; Ludzia, P (Springer Nature, 2020)
KKT4 is a kinetoplastid-specific microtubule-binding kinetochore protein that lacks significant similarity to any known kinetochore or microtubule-binding proteins. Here we present the 1H, 13C and 15N resonance assignments for several fragments from the microtubule-binding domain of KKT4 (KKT4115–343) from Trypanosoma brucei. These assignments provide the starting point for detailed investigations of the structure, dynamics and interactions of the microtubule-binding region of KKT4.